2021
DOI: 10.1016/j.oret.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Visual Acuity Outcomes after Anti–Vascular Endothelial Growth Factor Treatment for Macular Edema Secondary to Central Retinal Vein Occlusion

Abstract: Purpose To evaluate whether baseline demographic, clinical, and OCT characteristics predict visual acuity (VA) outcomes in patients receiving anti–vascular endothelial growth factor (VEGF) therapy for macular edema (ME) due to central retinal vein occlusion (CRVO). Design Post hoc analysis of the randomized noninferiority trial (Lucentis, Eylea, Avastin in CRVO) LEAVO Study from December 12, 2014, to December 16, 2016, carried out across 44 UK National Health Service op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 21 publications
(23 reference statements)
2
21
0
Order By: Relevance
“…We also found that an older age was associated with poorer BCVA at the initial examination. This was not too surprising because there have been many past studies reporting that an older age was associated with poorer final visual outcomes in eyes with CRVO [ 16 , 18 , 19 , 20 ]. We assume that the age-related sclerotic changes in the arteries, and the degenerative changes of the vessel walls may be associated with this finding.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We also found that an older age was associated with poorer BCVA at the initial examination. This was not too surprising because there have been many past studies reporting that an older age was associated with poorer final visual outcomes in eyes with CRVO [ 16 , 18 , 19 , 20 ]. We assume that the age-related sclerotic changes in the arteries, and the degenerative changes of the vessel walls may be associated with this finding.…”
Section: Discussionmentioning
confidence: 94%
“…It is known that the baseline best-corrected visual acuity (BCVA) is the strongest predictor for the final BCVA in eyes with CRVO [ 16 , 17 , 18 , 19 , 20 ]. Therefore, the factors involved in visual acuity at the baseline can be indirectly related to the final visual outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This was not too surprising because there have been many past studies reporting that an older age was associated with worse nal visual outcomes in eyes with CRVO. 16,[18][19][20] We presume that the age-related sclerotic changes in the arteries and the degenerative changes of the vessel wall may be associated with this result. On the other hand, we cannot rule out the possibility that the age-related mild cataract might have affected our results because we excluded CRVO patients with only severe cataracts (≥grade 3) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] It is known that the baseline best-corrected visual acuity (BCVA) is the strongest predictor for the nal BCVA in eyes with CRVO. [16][17][18][19][20] However, a PubMed search did not extract any study examining the background factors of the patients that were signi cantly associated with poorer BCVAs at the initial visit to the hospital. Thus, the purpose of this study was to determine the baseline characteristics of patients with a CRVO that were signi cantly associated with the baseline BCVA.…”
Section: Main Textmentioning
confidence: 99%
“…Sen et al investigated the association between several factors (independent variables) and visual acuity outcomes (dependent variable) in patients receiving anti-vascular endothelial growth factor therapy for macular oedema (DMO) by means of both linear and logistic regression [9]. Multivariable linear regression demonstrated that age (Estimate −0.33, 95% CI − 0.48 to −0.19, p < 0.001) was significantly associated with best-corrected visual acuity (BCVA) at 100 weeks at alpha = 0.05 significance level [9]. The regression coefficient of −0.33 means that the BCVA at 100 weeks decreases by 0.33 with each additional year of older age.…”
Section: Clinical Examplementioning
confidence: 99%